1993
DOI: 10.1172/jci116428
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of the renin-angiotensin system in human tissues. Quantitative analysis by the polymerase chain reaction.

Abstract: Activation of tissue-specific gene expression of the components of the renin-angiotensin system (RAS) in humans may play an important role in cardiovascular regulation and pathophysiology. Studies of human tissue RAS expression, however, have been limited by the lack of availability of sufficient amounts of fresh human tissues and a sensitive method for detecting specific mRNAs. To demonstrate the presence of components of local RASs in humans we used the polymerase chain reaction (PCR) after reverse transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
4

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(80 citation statements)
references
References 31 publications
2
74
0
4
Order By: Relevance
“…In addition, components of RAS could also be produced in some tissues (local RAS or tissue RAS), such as adipose tissue, brain, heart and so on. [11][12][13][14] Furthermore, Ang II can also be generated by enzymes of the nonrenin-angiotensin system, such as cathepsin D and cathepsin G. [15][16][17][18] So far, it is generally believed that Ang II is derived from AGT, irrespective of which way is chosen for its formation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, components of RAS could also be produced in some tissues (local RAS or tissue RAS), such as adipose tissue, brain, heart and so on. [11][12][13][14] Furthermore, Ang II can also be generated by enzymes of the nonrenin-angiotensin system, such as cathepsin D and cathepsin G. [15][16][17][18] So far, it is generally believed that Ang II is derived from AGT, irrespective of which way is chosen for its formation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that ANG I [13] and ANG II [39] are present in the placenta and the uteroplacental unit possesses all components of the RAS necessary for their generation [12]; renin [14], angiotensin [40] and ACE [15]. However, the impact of the altered RAS on the fetal side of the placenta is not well defined [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…M Angiotensin release from isolated vessels 16 and the presence of renin mRNA 17 in the blood vessel wall have been demonstrated in human tissue. However, the bulk of direct evidence for vascular angiotensin production has been derived from studies in rats.…”
Section: Discussionmentioning
confidence: 99%